9R, the cholinesterase and amyloid beta aggregation dual inhibitor, as a multifunctional agent to improve cognitive deficit and neuropathology in the triple-transgenic Alzheimer's disease mouse model. (15th December 2020) - Ju, Yaojun; Tam, Kin Yip
Abstract: Alzheimer's disease (AD) is the most common kind of dementia in the aging population leading to great social and financial burdens in many countries around the world. For decades, disease-modifying drug developed using the "one target, one drug" strategy failed to conquer this disease. Recently, we have designed and synthesized 9R, which exhibited dual inhibition of cholinesterase and amyloid beta (Aβ) aggregation in vitro . Herein, we evaluated the in vivo efficacy of 9R in a triple transgenic AD (3xTg-AD) mouse model. 3xTg-AD mice (10-month-old) were dosed intraperitoneally with 9R (daily 3, 10 or 30 mg/kg) for a month. Known cholinesterase inhibitor donepezil (0.3 mg/kg) and Aβ aggregation inhibitor tramiprosate (30 mg/kg) were used as positive controls. Cognitive performance of the mice was then evaluated by using Morris Water Maze (MWM), Y-maze tasks and Open Field test. The acetylcholine level, degree of Aβ deposition, amyloid precursor protein (APP) processing, neuroinflammation, tau deposition and tau hyperphosphorylation in the brains of the 3xTg-AD mice were examined. We have observed that one-month treatment with 9R significantly improved cognitive deficits in 3xTg-AD mice. Moreover, 9R treatment enhanced the brain acetylcholine level and mitigated the amyloid burden, tau hyperphosphorylation and neuroinflammation in the mouse brains. The effects of 9R on APP processing, neuroinflammation, tau hyperphosphorylation and Cdk-p25 action demonstrated its multifunctional role in 3xTg-AD mouse model. Our results suggested that the use of multi-target compound could be a potential approach to treat AD. Highlights: 9R improved cognitive impairments in 3 × Tg AD mice, outperforming positive controls. 9R raised acetylcholine level and reduced amyloid burden in brains of 3 × Tg AD mice. 9R modulated APP processing, neuroinflammation and tau phosphorylation in vivo . 9R relieved abnormal tau via reducing Cdk5-p25 activity in cell models of tauopathy.